The performance of the actor between theater and cinema (Romeo and Juliet as a model) - MOHAMMED RADHI, SAAD (International Journal of Psychosocial Rehabilitation, 2020)
The relationship between theater and cinema is old one. When the cinema was invented, especially the camera, the films were based on the theater. There was no editing; the film was shot in one play. When the montage was invented, it changed, and the film came out of theaters to public places and became a screenwriter, until it evolved to where we are now. Shakespeare, Ibsen, Cocteau, Tennessee Williams, Arthur Miller, and others have been presented in the cinema, as director Paz Luhrmann did when he introduced the play Romeo and Juliet with a new vision and a reversal of the original playtime. Shakespeare and dropped it on a certain reality and a specific time and spatial environment was the country in which he lives on the grounds that love stories are repeated every time and place, and here we will look for the nature of the performance of the actor between theater and cinema and what is the similarity and difference in his performance in both cases and the relationship and variables that occur in the play when The Night is to film. And looking for how to process the play and turn it into a movie? And how do cinematic techniques affect the performance of the actor? To what extent does the film preserve the original theater?